Integration of Photovoltaic Distributed Generation in Grid Distribution Network: A Literature Review - Maharmi, Benriwati; Syafii, Syafii; Azhari Zakri , Azriyenni (LPPM Universitas Andalas, 2023)
Distributed Generation (DG) will become a future generation system known as a renewable energy source. Renewable energy is a topic being developed due to being environmentally friendly. It fulfills the need for electrical energy to replace fossil energy sources to reduce climate change due to carbon emissions towards net-zero emissions by 2050, reducing climate change by 1.50 C to 20 C. Solar photovoltaic (PV) is an energy source that has been widely developed and has enormous potential; where PV can be integrated off the grid and on the grid. Integrating PV into the network is challenging, so the network remains stable and reliable due to intermittent energy generation. This paper reviews the integration of PV-DG distribution networks. Topology, optimization, and impacts on the distribution network are also discussed in this paper. The literature review results show that PV-DG integrated into the grid has an impact caused by intermittent PV generation.